Find the following: if f(x) = x²+1 and g(x)=2x-3
whats ==> (G*F)(2)

Find the following: if f(x) = x²+1 and g(x)=2x-3
whats ==> (G*F)(2)

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

(gf) (x) = (x^2+1)(2x-3)

G*F=2(x^2+1)-3

sub x=2
so 5(1)=5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.